Cloud and Weather Phenomena based on the Temperature Gradient - Yu-Cheng, Lu; Chun-Leung, Ho (TMAL02 Expert Conference, 2020)
Most of cloud and weather phenomena occur in the troposphere. With ISA atmosphere model by US Standard Atmosphere, we can obtain the temperature gradient in the atmosphere, which is an important cause of those phenomena. And combined with basic thermodynamics and meteorology knowledge, we can further know about the details of how clouds and weather phenomena occur and the influences to flight.